The history of the creation of dictionaries in English and Azerbaijani linguistics - Гусейновa, Л. (Journal of Oriental Studies, 2018)
The article deals with the history of the creation of dictionaries in English and Azerbaijani languages and found that the history of the creation of the English vocabulary has gone through a difficult path and, in contrast to previous years, has undergone a broader development path in modern times. Among other things, in the development of languages, an important role is played by Anglo-Azerbaijani, Azerbaijani- English phrase books of various types. All this gives grounds for believing that the dictionary business developed to a large extent not only in compiling dictionaries of English, but also in the Azerbaijani language, which could satisfy the readers’ need to a certain extent.